Penerapan Metode Drill untuk Meningkatkan Kemampuan Bina Diri Makan Siswa Tunagrahita di SMALB Negeri Ternate - Ruslia Ahadi (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study aims to determine whether the drill method can improve the self-cultivation ability of mentally retarded students at SMALB Negeri Ternate. The research method used in this research is the single subject experimental method or Single Subject Research (SSR). The design used in this study was the A-B-A design, which consisted of baseline-1, intervention, and baseline-2 phases, with a mentally retarded student of class XI at State Senior High School Ternate. Based on data analysis and research conducted, it is concluded that the Drill method can improve the self-cultivation ability of mentally retarded students at State Senior High School Ternate. This is indicated by data that overlap (overlap) in the analysis between conditions A1 / B and B / A2 at 0%, which means that the smaller the percentage of overlap, the greater the influence on the target behavior. This is also supported by an increase in the children's self-development ability scores during the baseline-1, intervention, and baseline-2 phases. The increase in this score shows that the ability of mentally retarded students to self-development can be improved using the Drill method